In vitro maturation of bubaline oocytes with buffalo estrous serum in presence or absence of hormones - KUMAR, SURESH; MAURYA, S N (The Indian Journal of Animal Reproduction, 2023)
The present investigation on in vitro maturation of buffalo oocytes was conducted on oocytes aspirated frombuffalo ovaries obtained from slaughter house. The study revealed that although the buffalo oocytes can be matured inTCM-199 and Ham's F-10 medium but addition of BES and hormones significantly (P
Keywords: Buffalo; oocytes; maturation